CONSUMER BEHAVIOR AND SUSTAINABLE PRODUCT ADOPTION IN ODISHA: A CASE STUDY - Sweeta Agrawal; Richa Sharma, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Modern sustainability initiatives are becoming increasingly influenced by consumer behaviour, as more people are becoming conscious of their environmental and social impacts. This research aims to investigate and compare the perception of consumers towards the acceptance of sustainable products among people in Odisha. By utilizing a mixed-methods approach, primary data was collected through structured surveys administered to consumers while secondary data was sourced from existing literature reviews. The study assessed the factors influencing the perception of these stakeholders towards sustainable products in Odisha. The data was analysed using SPSS software. The results showed that behavioural intention of stakeholders is significantly influenced by perceived environmental concerns, perceived safety, perceived ethical considerations, and perceived product quality. However, social influence does not have a significant impact on behavioural intention.